Contrasting Experiences: Understanding the Longer-Term Impact of Improving Access to Pre-Primary Education in Rural Indonesia. Issue 1 (2nd January 2021) - Hasan, Amer; Jung, Haeil; Kinnell, Angela; Maika, Amelia; Nakajima, Nozomi; Pradhan, Menno
Abstract: This paper examines the child development outcomes of two cohorts of children who were exposed to the same intervention at different points in time. One cohort was eligible to access playgroups during the first year of a five-year project cycle, beginning at age four. The other cohort became eligible to access these services during the third year of a five-year project cycle, beginning at age three. The younger cohort was more likely to be exposed to playgroups for longer and at more age-appropriate times relative to the older cohort. The paper finds that enrollment rates and enrollment duration in preprimary education increased for both cohorts, but the enrollment effects were larger for the younger cohort. In terms of child development outcomes, there were short-term effects at age five that did not last until age eight, for both cohorts. Moreover, the younger cohort had substantially higher test scores during the early grades of primary school, relative to the older cohort. We document the extent to which program impacts can vary as a result of differences in project implementation.